Global Financial Crisis and Islamic Bank Efficiency: Are Efficiencies Stable or Impacted? Evidence From Malaysian Islamic Banks - Samad , Abdus (Journal of Accounting and Finance, 2021)
In examining the impact of the global financial crisis on loan and deposit efficiencies, Data Development Analysis (DEA) is applied in estimating the technical efficiency of loans and deposits of the Islamic of Malaysia during 2008-2013. This study found that the average loan efficiency was 0.83., 0.88, 0.87, 0.95, 1.0, and 0.94 and the deposit efficiency was 0.87, 0.94, 0.94, 0.96, 0.92, and 0.96 during 2008-213 respectively. A comparison of two efficiencies found deposit efficiency dominated the loan efficiency. Second, in testing stability of the efficiencies, this paper used both parametric and the non-parametric tests, as suggested by Jarque Bera Test. Results of parametric test,( ANOVA F-test, t-test, and Welch F-test, and the non-parametric tests, Wicoxon/Mann-Whitney, Median Chi-square, performed on loans and deposits between the global financial crisis period and the post global financial crisis period, found no significant differences between efficiencies of the two period. The failure to reject the null hypothesis of the equality of the mean and median efficiencies between the global financial crisis and the post global financial crisis period suggests that the efficiencies of the Islamic banks of Malaysia are stable. The global financial crisis had no impact on the technical efficiencies of the Islamic banks of Malaysia.